Short‐Term Heparin Kinetics during Catheter Ablation of Atrial Fibrillation. Issue 10 (20th June 2015) - GABUS, VINCENT; ROLLIN, ANNE; MAURY, PHILIPPE; FORCLAZ, ANDREI; PASCALE, PATRIZIO; DHUTIA, HARSHIL; BISCH, LAURENCE; PRUVOT, ETIENNE
<x xml:space="preserve">Abstract</x> Background Percutaneous catheter ablation of atrial fibrillation (CA‐AF) is a treatment option for symptomatic drug‐refractory atrial fibrillation (AF). CA‐AF carries a risk for thromboembolic complications that has been minimized by the use of intraprocedural intravenous unfractionated heparin (UFH). The optimal administration of UFH as well as its kinetics are not well established and need to be precisely determined. Methods and Results A total 102 of consecutive patients suffering from symptomatic drug‐refractory AF underwent CA‐AF. The mean age was 61 ± 10 years old. After transseptal puncture of the fossa ovalis, weight‐adjusted UFH bolus (100 U/kg) was infused. A significant increase in activated clotting time (ACT) was observed from an average value of 100 ± 27 seconds at baseline, to 355 ± 94 seconds at 10 min (T10), to 375 ± 90 seconds at 20 min (T20). Twenty‐four patients failed to reach the targeted ACT value of ≥300 seconds at T10 and more than half of these remained with subtherapeutic ACT values at T20. This subset of patients showed similar clinical characteristics and amount of UFH but were more frequently prescribed preprocedural vitamin K1 than the rest of the study population. Conclusions In a typical intervention setting, UFH displays unexpected slow anticoagulation kinetics in a significant proportion of procedures up to 20 minutes after infusion. These findings support the infusion of UFH before transseptal puncture or any left‐sided catheterization with early ACT measurements to identify patients with delayed kinetics. They are in line with recent guidelines to perform CA‐AF under therapeutic anticoagulation.